2014
DOI: 10.1371/journal.pone.0096029
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from the Variable Region of Specific Antibodies Are Shared among Lung Cancer Patients

Abstract: Late diagnosis of lung cancer is still the main reason for high mortality rates in lung cancer. Lung cancer is a heterogeneous disease which induces an immune response to different tumor antigens. Several methods for searching autoantibodies have been described that are based on known purified antigen panels. The aim of our study is to find evidence that parts of the antigen-binding-domain of antibodies are shared among lung cancer patients. This was investigated by a novel approach based on sequencing antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Overall, 1,380 publications that did not meet the inclusion criteria were excluded based on the titles and abstracts. Among the remaining 77 full-text articles, 7 were excluded because no outcomes of interest were reported [ 20 26 ], 3 were excluded because the participants were not evaluated for serum autoantibodies [ 27 29 ], 2 were excluded because it was neither in English or Chinese [ 30 , 31 ]. One article was excluded because the autoantibody was not performed in the serum [ 32 ], and another one was excluded because of duplicate data [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 1,380 publications that did not meet the inclusion criteria were excluded based on the titles and abstracts. Among the remaining 77 full-text articles, 7 were excluded because no outcomes of interest were reported [ 20 26 ], 3 were excluded because the participants were not evaluated for serum autoantibodies [ 27 29 ], 2 were excluded because it was neither in English or Chinese [ 30 , 31 ]. One article was excluded because the autoantibody was not performed in the serum [ 32 ], and another one was excluded because of duplicate data [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hints that support such assumptions come from other studies that show the diseasespecific accumulation of distinct complementarity determining region peptides (CDR peptides) of the highly variable region of AAbs in glaucoma and other diseases. [43][44][45] From these findings, it seems likely that not only alterations of the antigen but also of the AAbs themselves can lead to the onset of autoimmune processes. This raises an interesting question for future studies that aim to analyse whether alterations of either antibody or target protein can influence the binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis that needs further validation by subsequent experiments is that not only quantitative but also qualitative differences between natural and disease‐related AAbs may play a role. Hints that support such assumptions come from other studies that show the disease‐specific accumulation of distinct complementarity determining region peptides (CDR peptides) of the highly variable region of AAbs in glaucoma and other diseases . From these findings, it seems likely that not only alterations of the antigen but also of the AAbs themselves can lead to the onset of autoimmune processes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hong et al also found that 131I-anti-ProGRP(31–98)scFv, which can bind to progastrin-releasing peptide(31–98) (ProGRP(31–98)), had a high level of selective uptake by tumor tissues, but a low level in normal tissues, indicating that it could be used for SCLC radioimmunoimaging [ 62 ]. Impressively, de Costa et al first found that peptides generated from variable antibodies were shared among lung cancer patients but not a control group [ 25 ], suggesting that these peptides could be novel biomarkers for screening lung cancer. Evidence also showed that the peptide HCBP-1 has exhibited specific binding to lung cancer stem cells, suggesting that this peptide may be used to identify lung cancer stem cells and as a drug carrier to lung cancer stem cells [ 26 ].…”
Section: Peptides and Lung Cancermentioning
confidence: 99%